JURIDICAL ANALYSIS OF RESPONSIBILITY PERPETRATOR OF THE CRIME FORGERY OF LETTERS UNDER DURESS AS AN EFFORT TO ENTER INTO SAME-SEX MARRIAGE: CASE STUDY - Disna Dwi Kusuma; Emi Puasa Handayani; Nur Chasanah (SYNTIFIC, 2023)
Background. The criminal liability of the perpetrator of forgery of letters to carry out same-sex marriages which are now starting to occur by considering the judge’s ratio decidendi. The purpose of this study is to analyze the mens rea in Article 48 of the Criminal Code on coercion against the actions of the perpetrators of verdict number 155/Pid.B/2017/PN.Pwr and number 134/Pid./2017/PN.Byl and to examine the ratio decidendi of the judge in deciding the case of forgery of letters in case number 155/Pid.B/2017/PN.Pwr and number 134/Pid./2017/PN.Byl. Research Method. This research used normative juridical methods with a statue approach and case study approach. This research using literature and regulations that relevant to the topic or research problem criminal liability for perpetrators of mail forgery. Findings. The results of the author's research on decision number 155/Pid.B/2017/PN.Pwr and decision number 134/Pid./2017/PN.Byl are that the defendant's mens rea does not fulfill the elements of Article 48 of the Criminal Code so that there are no justification and excuse reasons that make the defendant free from the charges, therefore the defendant for all his actions must be accountable. Conclusion. The judge's ratio decidendi for both decision number 155/Pid.B/2017/PN.Pwr and decision number 134/Pid./2017/PN.Byl was correct and in accordance with the legislation.